Understanding GIS through sustainable development goals : case studies with QGIS - Holloway, Paul (Boca Raton, FL : CRC Press, 2023)
'This book applies a pedagogical shift to learning GIS as readers employ the concepts and methodologies on real-world problems. This book provides 16 case studies with step-by-step instructions using QGIS, an open-source software. Readers develop GIS skills while learning the fundamentals of spatial data models, projections, and spatial databases, different cartographic methods, such as graduated symbology, change maps, and dynamic visualization, as well as advanced spatial analysis like geoprocessing, multiple criteria analysis, and spatial statistics. The topics chosen are taught in secondary and tertiary education institutions making this a textbook for all students and educators'--
OCLC-licensed vendor bibliographic record.
Keywords: QGIS (Computer file); Geographic information systems -- Study and teaching; Spatial analysis (Statistics) -- Methodology; Sustainable development